Talent Management in Higher Education Institutions: Developing Leadership Competencies - Mohamed Jais, Ismie Roha; Yahaya, Nordin; Ghani, Erlane K (Journal of Education and e-Learning Research, 2020)
This paper presents the development process of talent management in higher education institutions. Specifically, this study aims to identify clusters that best fit the leadership competency framework for those institutions. This study utilizes the qualitative approach via focus group discussion with the Leadership Competency and Instrument Committee in AKEPT, and also by interviews with academics in the public universities. The findings from the focus group discussion and interview demonstrate five clusters of leadership competency skills framework: personnel effectiveness, cognition, leading, impact and influence, and achievement and action. Within these clusters, issues were identified that need to be taken into consideration when selecting future leaders in higher education institutions. Based on the findings, a set of attributes were listed that can be adopted in the future to allow leaders of higher institutional education to enhance their sustainability performance. This paper provides an understanding to interested parties on the attributes of good leaders for higher education institutions.